Seeking a path of its own: Old Testament ethics in current research - D.G. Firth (Acta Theologica)
Old Testament ethics has been a Cinderella discipline. However, since the 1980s, it has emerged as an important area of study, albeit one where certain key questions continue to be unresolved, including: Is this a discipline in its own right? Is Old Testament ethics a descriptive or normative discipline? If so, which texts does it consider? If it does contribute to contemporary practice, by what mode is that determined? This article outlines the issues involved in each of these questions, exploring a path towards understanding Old Testament ethics as a distinct discipline that draws on the whole canon with the aim of shaping contemporary practice, while accepting that fundamental differences continue.